Bank Liquidity Creation and Risk-Taking: Does Managerial Ability Matter? - Andreou, Panayiotis; Philip, Dennis; Robejsek, Peter (My University, 2016)
This study investigates the impact of managerial ability on banks' liquidity creation and risk-taking behavior. We find that higher ability managers create more liquidity and take more risk. During times of financial crisis, however, higher ability bank managers reduce liquidity creation as a way to de-leverage their balance sheets. Our findings inform recent theoretical and empirical studies that investigate determinants of liquidity creation and risk by introducing managerial ability as a prominent antecedent of the banks' intermediation and risk-transforming service. Moreover, this study has policy-related implications, since managerial ability can be quantified as a key performance indicator for prudential supervision of banks and could help regulators to target intervention efforts more purposefully during times of crisis.
Keywords: Financial crisis; Financial institutions; Liquidity creation; Managerial ability; Risk-taking